Synthesis of ZSM-5 zeolite from South African fly ash and its application as solid catalyst - Missengue-Na-Moutoula, Roland (University of the Western cape, 2017)
Philosophiae Doctor - PhD === Zeolites are widely used as environmentally friendly solid catalysts or catalyst supports in the refining and petrochemical industries. ZSM-5 zeolite is composed of a three-dimensional medium pore structure (openings of 5-5.5 Å) with high silica content, high temperature stability and strong acidity making it a well-known and an established catalyst for several petroleum derived chemical processes such as cracking, aromatic alkylation, disproportionation, Methanol-to-Gasoline, isomerisation, etc. Nowadays, the synthesis of ZSM-5 zeolite from silica, alumina sources and structure directing agents (templates) is well known. Its synthesis is possible from fly ash, which is a low cost source of both silica and alumina. Fly ash is an inorganic residue resulting from the combustion of coal in electricity generating plants, consisting mostly of SiO₂ and Al₂O₃. ZSM-5 zeolite has not been synthesised from South African coal fly ash and the literature reports that fly ash-based ZSM-5 zeolite was synthesised only with tetrapropylammonium (TPA+) as structure directing agent and required an excessive amount of additional silica. The final ZSM-5 product was reported to still contain fly ash mineral phases after synthesis. This prevents the use of fly ash as a ZSM-5 zeolite precursor. Moreover, the synthesis of a high purity ZSM-5 zeolite from fly ash without additional silica has not been yet reported. This study aimed to synthesise high purity ZSM-5 zeolite from South African coal fly ash without additional silica, and with tetrapropylammonium bromide (TPABr), 1,6- hexanediamine (HDA) or 1-propylamine (PA) as structure directing agent. This aim was achieved by first optimising the synthesis of ZSM-5 zeolite from South African coal fly ash based on a formulation reported in the literature with fumed silica and TPABr as additional source of silica and structure directing agent respectively. Thereafter, the obtained optimum conditions were used to synthesise other fly ash-based ZSM-5 zeolite products by substituting TPABr with HDA or PA. Two routes of treating the as-received fly ash prior to the hydrothermal synthesis were applied in order to improve the quality of the final products or reduce the amount of the fumed silica that was used. The first route consisted of treating the as-received fly ash with concentrated H₂SO₄ in order to remove a certain amount of aluminium and increase the Si/Al in the acid treated fly ash solid residue but also remove some other elements such as Fe, Ca, Mg, and Ti which might have an undesirable effect on the product quality. The acid treated fly ash solid residue was used as ZSM-5 precursor with fumed silica as additional silica source and TPABr, HDA or PA as structure directing agent. The ZSM-5 zeolite products that were synthesised from the as-received fly ash as well as from the H₂SO₄ treated fly ash were treated with oxalic acid solution in order to reduce the aluminium content in the final products. The second route consisted of fusing the as-received fly ash with NaOH and treating the powder fused fly ash extract with oxalic acid solution. The obtained fused and oxalic acid treated fly ash extracts were used as ZSM-5 precursors without additional fumed silica and with TPABr, HDA or PA as structure directing agent. ZSM-5 zeolite was synthesised from the as-received South African coal fly ash not only with the commonly used structure directing agent TPABr but also with two other, lower cost structure directing agents, HDA and PA. The synthesis process did not generate any solid waste as fly ash was used as bulk, which could be a way of valorising South African coal fly ash. However, the final products contained some fly ash mineral phases such as mullite and quartz, and had poor physical and chemical properties compared to a commercial H-ZSM-5 zeolite. The treatment of the as-received fly ash with H₂SO4 resulted in fly ash-based ZSM-5 zeolite products with better physical and chemical properties than those of ZSM-5 zeolite products that were synthesised from the as-received fly ash. Moreover, the post-synthesis treatment of the fly ash-based ZSM-5 zeolite products with oxalic acid resulted in an increase in the Si/Al ratio, offering a post-synthesis route to adjust the acidity of the catalysts. However, mullite and quartz phases were still present in the synthesised products. Alternatively, high purity ZSM-5 zeolite was synthesised from the fused and oxalic treated fly ash extracts without additional silica and with TPABr, HDA or PA as structure directing agent. Moreover, these synthesised fly ash-based ZSM-5 zeolite products had similar physical and chemical properties to the commercial H-ZSM-5 zeolite. The synthesised fly ash-based ZSM-5 zeolite products were used as solid catalysts in the Methanol-to-Olefins (MTO) and Nazarov reactions. The ZSM-5 zeolite products that were synthesised from the H₂SO4 treated fly ash as well as fused and oxalic treated fly ash were successfully used as solid catalysts in the MTO and Nazarov reactions. The ZSM-5 zeolite products that were synthesised from the H₂SO₄ treated fly ash presented a similar trend in MTO and Nazarov reactions depending on the structure directing agent that was used, and the ZSM-5 zeolite that was synthesised with HDA as structure directing agent had the highest MTO and Nazarov conversion. However these catalysts deactivated more quickly compared to the commercial H-ZSM-5 zeolite. On the other hand, the zeolites that were synthesised from the fused and oxalic acid treated fly ash had a high initial MTO conversion equivalent to the commercial H-ZSM-5 zeolite. However, they deactivated after 5 h of time on stream due to diffusional constraints, because of their large crystal sizes. This study developed novel routes in the synthesis of high value zeolites from fly ash. ZSM-5 zeolite was synthesised from fly ash with structure directing agents other that TPA+ cation and had acceptable Brønsted acidity and high initial conversion in MTO and Nazarov reactions. This has not been yet reported in the literature. Moreover, for the first time a high purity ZSM-5 zeolite was synthesised from fly ash without additional silica and had similar properties to a commercial H-ZSM-5 zeolite. This constituted a breakthrough in the fly ash-based ZSM-5 zeolite synthesis procedure, which will promote the valorisation of fly ash through ZSM-5 synthesis due to avoiding the addition of silica source in the hydrothermal gel and preventing the presence of fly ash mineral phases in the final products. This study can have a significant economic and environmental impact in South Africa if the synthesis process is scaled up as it provides a potentially cheap and innovative way of using waste for making a high value green and acid catalyst, namely ZSM-5 zeolite that has several catalytic applications; and it promotes the valorisation of South African coal fly ash that is considered by many as waste material. === National Research Foundation (NRF)